Assessment of the quality and content of clinical practice guidelines (CPGs) for vitamin D and for immigrants using the AGREE-II instrument: a protocol for systematic review - Yousef, Said; Hayawi, Lamia; Manuel, Douglas; Colman, Ian; Papadimitropoulos, Manny; Hossain, Alomgir; Faris, Moez A.; Wells, George A. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Introduction Worldwide, more immigrants experience vitamin D (vitD) deficiency than non-immigrants, which is attributed to ethnic variations, place or region of birth, skin pigmentation, clothing style, and resettlement-related changes in diet, physical activity, and sun exposure. Current recommendations in clinical practice guidelines (CPGs) concerning vitD are inadequate to address vitD deficiency among immigrants. CPGs may also lack guidance for physicians on vitD supplementation for immigrants. Moreover, there are concerns about the overall quality of these CPGs. Objectives This systematic review will collate and critically appraise CPGs relevant to immigrants’ health and vitD. Moreover, we will evaluate whether the CPGs of vitD including recommendations for immigrants and clarify whether the CPGs of immigrants include recommendations on vitD. Methods A systematic search of Ovid MEDLINE® ALL, EMBASE, and Turning Research Into Practice (TRIP) electronic databases, guideline repositories, and gray literature will be conducted to identify relevant CPGs. Two reviewers will independently evaluate the methodological quality of the retrieved guidelines using the Appraisal of Guidelines, Research, and Evaluation-II (AGREE-II) instrument. CPGs scoring ≥60% in at least four domains, including “rigor of development,” will be considered high quality. Conclusion Evaluating the quality and content of relevant CPGs may support researchers in developing national and global guidelines for immigrants. Furthermore, it may support vitD testing, nutritional counseling, and supplementation for vulnerable immigrant sub-populations. Systematic review registration PROSPERO CRD42021240562.